2012
DOI: 10.3389/fimmu.2012.00120
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell: An Emerging Partner in Immune Interaction

Abstract: Mast cells (MCs) are currently recognized as effector cells in many settings of the immune response, including host defense, immune regulation, allergy, chronic inflammation, and autoimmune diseases. MC pleiotropic functions reflect their ability to secrete a wide spectrum of preformed or newly synthesized biologically active products with pro-inflammatory, anti-inflammatory and/or immunosuppressive properties, in response to multiple signals. Moreover, the modulation of MC effector phenotypes relies on the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
103
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(106 citation statements)
references
References 117 publications
(125 reference statements)
1
103
0
2
Order By: Relevance
“…Mast cells were first found to release histamine granules in immediate hypersensitivity reactions; however, recent research has revealed that mast cells are involved in a variety of immune responses, including host defense, immune regulation, allergy, chronic inflammation, and autoimmune disease. 8 In response to IgE stimulation, mast cells secrete various mediators, including T helper 2 cytokines and regulatory cytokines. 9 Non-specific IgE alone can induce cytokine secretion independent of any antigen.…”
mentioning
confidence: 99%
“…Mast cells were first found to release histamine granules in immediate hypersensitivity reactions; however, recent research has revealed that mast cells are involved in a variety of immune responses, including host defense, immune regulation, allergy, chronic inflammation, and autoimmune disease. 8 In response to IgE stimulation, mast cells secrete various mediators, including T helper 2 cytokines and regulatory cytokines. 9 Non-specific IgE alone can induce cytokine secretion independent of any antigen.…”
mentioning
confidence: 99%
“…Mast cells respond to antigenic stimulation through the cross-linking of immunoglobulin E (IgE) bound to high-affinity receptors for IgE (FcεRI) and the activation of the FcγR after IgG binding (reviewed in [1,2]). Upon activation, mast cells release either preformed, granule-stored mediators, such as histamine and proteases, or newly generated mediators, such as eicosanoids, cytokines, and chemokines [3].…”
Section: Introductionmentioning
confidence: 99%
“…Matsuda ve arkadaşları yaptıkları deneysel bir çalışmada; genetik olarak mast hücreleri eksik farelerde kene enfestasyonuna karşı direnç gelişiminde hata oluşurken doğru yanıtın ancak mast hücre ve IgE'nin beraber varlığında mümkün olduğunu göstermişler ve sonuçta tip 1 aşırı duyarlılık yanıtlarının organizma için fizyolojik bir rolü de olduğu sonucuna varmışlardır 17 . Alerjik inflamasyon dışındaki inflamasyonda mast hücrelerinin rolü Mast hücreleri uyaranın tipi ve özelliğine bağlı olarak çeşitli biyolojik aktif ürünler üreterek, tetikleme ya da baskılama yoluyla, bağışıklık yanıtlarının üzerinde önemli etkilere sahiptir 10 . Bu hücreler doğal bağışıklıkta bakteri, virüs ve parazitlere karşı geliştirilen konak savunmasında önemli rol oynar 14 .…”
Section: Introductionunclassified
“…Mast hücreleri ayrıca ürettikleri çeşitli sitokinler ile B hücre gelişimi ve fonksiyonları üzerinde de etki gösterirler. B hücreleri ile ilişkileri sonucu, özellikle IL-4 varlığında; IgE üretimini indüklerler 10 . Mast hücreleri aynı zamanda antiinflamatuar ve immunsupresif etkileri olan hücrelerdir.…”
Section: Introductionunclassified